2000
DOI: 10.1260/0958305001500112
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Patterns of Fuel and Wood Use by Households in Rural Zimbabwe

Abstract: A questionnaire survey of fuel and wood use was administered to approximately 1500 households in rural Zimbabwe in 1994 and repeated in 1999. The nine localities covered by the survey fell into four strata distinguished by woodland cover, distance from urban centres and whether communal or resettlement (ex-commercial farming) areas. Over time household assets increased, but incomes remained constant in all but one stratum. Simultaneously wood became scarcer according to respondents. In all four strata firewood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 16 publications
4
23
0
Order By: Relevance
“…About 97% and 94% of households collected fuelwood in 1991 and 2002, respectively, while the percentage of households purchasing fuelwood rose from 27% in 1991 to 31% in 2002. The slight increase in the percentage of households purchasing fuelwood possibly indicates that there was an increase in fuelwood scarcity in the local environment around the settlements (Vermeulen et al, 2000), corroborated by the 12% increase (approx. 30 min) in mean duration of fuelwood collection trips (Fig.…”
Section: Prevalence Of the Different Fuel Typesmentioning
confidence: 91%
See 3 more Smart Citations
“…About 97% and 94% of households collected fuelwood in 1991 and 2002, respectively, while the percentage of households purchasing fuelwood rose from 27% in 1991 to 31% in 2002. The slight increase in the percentage of households purchasing fuelwood possibly indicates that there was an increase in fuelwood scarcity in the local environment around the settlements (Vermeulen et al, 2000), corroborated by the 12% increase (approx. 30 min) in mean duration of fuelwood collection trips (Fig.…”
Section: Prevalence Of the Different Fuel Typesmentioning
confidence: 91%
“…Purchased fuelwood in these two settlements was more expensive than in the other three settlements. Despite the increase in fuelwood scarcity, the majority of households continued using wood as their main source of energy for thermal applications, as was reported by Vermeulen et al (2000) in Zimbabwe.…”
Section: Prevalence Of the Different Fuel Typesmentioning
confidence: 97%
See 2 more Smart Citations
“…The decline in woodland resources translates into additional labour required to extract woodland products. In environments like Chivi in 1994 most households reported that it took under two hours for a firewood collection trip, while in 1999 it was more than two hours (Vermeulen et al 2000 -Chivi was one of the study sites). Romwe is more heavily wooded than Mutangi (Kwesha and Mapaure 2001).…”
Section: Woodlandmentioning
confidence: 99%